The ongoing convergence of blended learning classroom in new normal: Teachers’ and students’ perspectives in higher education - Ramli Ramli; Farid Helmi Setyawan; Ridwan Ridwan; Nofvia De Vega; Romlah Ulfaika (EduLite: Journal of English Education, Literature and Culture, 2022)
Since Covid-19 was declared a pandemic, educational technology has become trended by playing E-learning. Teachers and students are forced to transform from traditional classes into E-classrooms. However, full e-learning did not give students a massive impact yet, and lately, they have become less motivated since it provided no real communication (Mese & Sevilen 2021). Integrating face-to-face learning (direct interaction) and technology-based learning (digital communication) becomes promising (Garrison &Vaughan, 2008; Rianto, 2020). This study explored the perspectives of 3 pre-service teachers and 27 students towards the blended learning (BL) practices in the EFL context. The setting was the English education department, Universitas Borneo Tarakan. The data were collected using online interviews to gain in-depth information. The findings uncovered that the teachers and students gave positive perspectives to apply this model to the new normal. In addition, BL could reshape the teachers' roles by applying multiple technology use in the teaching and learning process. BL  was also able to broaden students' learning experience and provide them with a technology-based world. This study highlighted some implications, including the need for pre-service teachers' professional development that ultimately will help teachers assist students in succeeding in blended learning.